1991
DOI: 10.1177/107110079101200104
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Isolated Talocalcaneal Fusion on Contact in the Ankle and Talonavicular Joints

Abstract: A cadaveric model was developed to establish the articular contact area and load distribution in the ankle joint, posterior facet of the talocalcaneal joint, and talonavicular joint using pressure sensitive film. Positions of dorsiflexion, neutral, and plantarflexion were evaluated. This model was further used to determine the effect of talocalcaneal fusion on the articular contact area in the talonavicular and ankle joints. Alteration of articular contact was most pronounced in the talonavicular joint. There,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
16
0
2

Year Published

1996
1996
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(22 citation statements)
references
References 11 publications
3
16
0
2
Order By: Relevance
“…Loading of the unfused foot resulted in 75% of the applied load detected by the pressure sensor on the talar dome in each loading position, consistent with previous studies [4,34]. Applied loading in the inverted and everted foot positions has been associated with variation in the mediolateral location of contact in the ankle in unfused, intact feet; such changes in contact location were not significant in our tested specimens (Fig.…”
Section: Discussionsupporting
confidence: 90%
“…Loading of the unfused foot resulted in 75% of the applied load detected by the pressure sensor on the talar dome in each loading position, consistent with previous studies [4,34]. Applied loading in the inverted and everted foot positions has been associated with variation in the mediolateral location of contact in the ankle in unfused, intact feet; such changes in contact location were not significant in our tested specimens (Fig.…”
Section: Discussionsupporting
confidence: 90%
“…These are provided both for the tibial mortise and for the trochlea tali, at five representative flexion (Pl/Do) positions along the full range of motion, and for the three specimens A, B and C. Position and size of the reported tibiotalar contact areas compare limitedly well with the literature. Significant size changes with flexion (Beaudoin et al, 1991;Kura et al, 1998) and maximum size in neutral position (Driscoll et al, 1994) were previously reported. The invasive techniques utilised, associated with the use of pressure-sensitive films, but mainly the loading conditions adopted in these studies make inappropriate any more detailed comparisons of the results.…”
Section: Discussionmentioning
confidence: 65%
“…For the contact at the tibiotalar joint, many experimental studies have been reported in the literature (Beaudoin et al, 1991;Bertsch et al, 2001;Calhoun et al, 1994;Clarke et al, 1991;Curtis et al, 1992;Driscoll et al, 1994;Earll et al, 1996;Friedman et al, 2001;Hartford et al, 1995;Kimizuka et al, 1980;Macko et al, 1991;Michelson et al, 2001;Pereira et al, 1996;Ramsey and Hamilton, 1976;Steffensmeier et al, 1996;Tarr et al, 1985;Thordarson et al, 1997;Ting et al, 1987), particularly looking at the effect of joint flexion position, joint loading, and integrity of the ligaments. Most of these are limited by the invasive measuring devices, i.e.…”
Section: Introductionmentioning
confidence: 98%
“…andere Hilfsmittel gemacht wurden, ist der Fuß nach wie vor ungeschützt [51]. [4,30], verglichen mit 1120 mm 2 für das Knie [25] und 1100 mm 2 für das Hüftgelenk [7]. Obwohl der "In-vivo-Kontaktstress" im Sprunggelenk noch nicht gemessen wurde, muss man davon ausgehen, dass bei gleicher Belastung der durchschnittliche Kontaktstress im Bereich des Sprunggelenks höher ist als im Bereich des Knie-und Hüftgelenks.…”
Section: Arthrose Des Osg Charakteristikaunclassified